THU0020 Fatigue and Mental Disorders in Sjogren's Syndrome. (10th June 2014) - Shelomkova, O.; Veltishchev, D.; Lisitsyna, T.; Vasiliev, V.; Kovalevskaya, O.; Seravina, O.; Krasnov, V.; Nasonov, E.
Abstract : Background: The physical and mental well being of patients with primary SS are significantly reduced [1]. Among the most significant causes are mental disorders and chronic fatigue, diagnosed in most patients suffering SS [2, 3, 4]. In the results of some previous studies fatigue had direct correlations with the diagnosis of depressive disorders but not with eyes/mouth dryness or immunology markers [3, 5]. Objectives: To evaluate the occurrence rate/severity of fatigue and its relations with the severity of depression, anxiety and some clinical manifestations in SS patients. Methods: 80 inpatients (mean age 46, 2±12, 3 yrs) suffering SS were enrolled in the study. Mental disorders (MD) were diagnosed in accordance with ICD-10 criteria. Mean age of patients during MD and SS manifestation - 31, 18±14, 6 and 34, 6±13, 3 acc. The severity of depression, anxiety, stress and fatigue were measured by HADS, MADRS, HAM-A, PSS-10 and FSS. Results: Among the patients complaints had prevailed headaches (33.7%), eyes and mouth dryness (42.5%, 53.7%), memory decline (73.7%) and fatigue (93.75%). The severe fatigue (FSS) was revealed in 72.5% patients. FSS correlated with the depression severity (MADRS) (r=0.22), complaints on eyes dryness (r=0.26), cryoglobulins (r=0, 25) level. The FSS score had significant correlations with anxiety and depression severity (HADS (r=0.38), WBI-WHO-5 (r=-0.52), HAM-A (r=0.34), MADRS (r=0.42) scores) and also menopausal period (r=0.32). MD were diagnosed in 78 (97.5%) of SS patients: depressive episode (mild/moderate; single/recurrent, n=27; 33.7%); dysthymia (n=12;15%); generalized anxiety disorder (n=9;11.3%); adjustment disorder (n=11;13.7%); schizotypal disorder (SD) (n=19;23.75%). Mean age of SS had significant direct correlation with the mean age of MD (r=0.82) manifestation. However, eyes/mouth dryness, immune disturbances, diagnosis of generalized vasculitis and lymphoma had pronounced correlations with the severity of anxiety and depression (MADRS and HAM-A scores). The significant differences in the occurrence rate of severe fatigue in different MD were not revealed. Conclusions: Fatigue has significant associations both as with MD diagnosis (anxiety and depressive disorders) as clinical manifestations of SS. References: Valtysdottir S.T., Gudbjornsson B., Lindqvist U, at al. Anxiety and depression in patients with primary Sjogren's syndrome. J Rheumatol. 2000;27:165 9. O Shelomkova, D Veltishchev, T Lisitsyna, V Vasiliev, O Kovalevskaya, O Seravina, V Krasnov, E Nasonov. Stress factors and mental disorders in Sjogren's syndrome: clinical-psychopathological and psychological analysis. J. Soc. I Clin. Psychiatry. 2013 (3): 36-42. Barendregt P., Visser M., Smets E. Fatigue in primary Sjögren's syndrome. Ann Rheum Dis. 1998 May; 57(5): 291–295. Segal B, Thomas W, Rogers T, at al. Prevalence, severity, and predictors of fatigue in subjects with primary Sjögren's syndrome. Arthritis Rheum.2008 Dec 15;59(12):1780-7. Tensing EK, Solovieva SA, Tervahartiala T, Nordstrom DC, Laine M, Niissalo S, Konttinen YT. Fatigue and health profile in sicca syndrome of Sjogren's and non-Sjogren's syndrome origin. Clin Exp Rheumatology. 2001;19:313–316 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4510